Jurisprudential Analysis of the Execution of the Inheritance of Adopted Children - Ahmad Akhsin (Law Development Journal, 2020)
The issues raised in This research is: What is the legal basis for the consideration of the Judge and the ijtihad style of the Religious Court Judges at the Batang Religious Court in settling the inheritance of adopted children? What factors influence the style of the decision of the Batang Religious Court Judge in the settlement of the case of adoptive son inheritance? The method used in this research is a normative juridical approach and the research specification uses descriptive analytical.The main tasks of the judiciary in Indonesia in receiving, examining, adjudicating and resolving any problems raised are carried out by judges. Judges here, apart from functioning as law enforcers, are also required to enforce law and justice. Here the judge will be required to do not just as a mouthpiece or mouthpiece Law, but more than that it is required to explore the law in every decision for the sake of upholding justice. In matters where there is no sharih text, the judge's ijtihad style is characterized by the use of unwritten sources of law, including istishhab and maslahah mursalah. Although it was not explicitly stated in the consideration of the decision, contextually ishtishhab was used as an unwritten source in the settlement of the case of the inheritance of adopted children. The Panel of Judges at the Batang Religious Court in the settlement of the case of the inheritance of adopted children who get inheritance rights through the mandatory will use ijtihad integrative between ijtihad intiqa'i and ijtihad insya'i according to the concept of Yusuf Al Qardawi, Meanwhile, the factors that influence the style of the judge's decision at the Batang Religious Court consist of two factors, internal and external factors of the judge, each of which has a dominant influence.Key Words: Jurisprudence; ijtihad; inheritance; adopted children; mandatory will